The Philosophy of Islamic Education: Its Nature, Scope, and Role in Building an Islamic Educational System - Nur Ali Yasin (At-Takwin: Journal of Islamic Education Studies, 2025)
This study aims to examine the nature and scope of Islamic educational philosophy through a qualitative approach with a library research method. Islamic educational philosophy is a conceptual foundation that combines philosophical principles with Islamic teaching values ​​in formulating educational goals, content, methods, and orientation. This study highlights three main aspects: the definition of Islamic educational philosophy, its scope which includes ontological, epistemological, and axiological aspects, and its role in forming a holistic and transcendental educational paradigm. The analysis was carried out descriptively-analystically on classical and contemporary literature sources. The results of the study indicate that Islamic educational philosophy plays an important role in formulating the direction of education that is not only pragmatic, but also rooted in the values ​​of divinity, humanity, and the sustainability of civilization. Thus, Islamic educational philosophy becomes the basic framework in developing an integral and character-based education system.